Correction: Barriers and facilitators to implementing six monthly multi-month dispensing of antiretroviral therapy in two urban HIV clinics during the COVID-19 Era in Malawi. - PLOS Global Public Health Editors (PLOS Global Public Health)
[This corrects the article DOI: 10.1371/journal.pgph.0003900.].